The Effect of Sodium Alginate Coating Containing Citrus (Citrus aurantium) and Lemon (Citrus lemon) Extracts on Quality Properties of Chicken Meat - Zahra Panahi; Rahem Khoshbakht; Bahareh Javadi; Emadodin Firoozi; Niloufar Shahbazi (Journal of Food Quality, 2022)
The effect of sodium alginate-based edible coating containing 2% citrus (Citrus aurantium) and lemon (Citrus lemon) extracts was evaluated on the chemical, antimicrobial, and sensory properties of samples during storage at 4°C. The results showed that coating with sodium alginate containing citrus and lemon extracts had a significant effect on the pH, TVN, PV, and TBA values of chicken meat (P<0.05). The lowest PV and TBA values were observed in the coated sample containing sodium alginate with 2% citrus and lemon extracts (ALG + CAE + CLE), indicating the antioxidant activity of sodium alginate and extracts. Coating resulted in less growth of microorganisms in the samples. The lowest microbial counts were also observed in the sodium alginate containing 2% citrus and lemon extracts (ALG + CAE + CLE). The coated samples had good overall acceptability similar to the control treatment. In conclusion, sodium alginate containing citrus (C. aurantium) and lemon extracts (C. lemon) are suggested for coating meat products.